PENERAPAN MODEL PEMBELAJARAN ARCS (ATTENTION, RELEVANCE, CONFIDENCE, SATISFACTION) TERHADAP PEMBELAJARAN FABEL DI SMP/MTs KELAS VII - Abdul Azis Khoiri (MEDIA DIDAKTIKA, 2018)
The purpose of this research is to describe the application ARCS model of fable in Class VII-k MTsN 1 Lamongan. This research is a qualitative descriptive quantitative. The instrument used in the research were observational, questionnaire, written test and interviews. The result of the study shows that the design used is by using RPP (lesson plan) with 4 indicators from ARCS model. The process of this study can be known by see the result of pre-test and post-test, for student’s respond increases 33,333% to be high category with percentage 48,485% and for student’s motivation to learn increases from 33,333% to be high percentage 48,485%.